Deferiprone does not protect against chronic anthracycline cardiotoxicity in vivo - Popelová, Olga; Sterba, Martin; Simůnek, Tomás; Mazurová, Yvona; Guncová, Ivana; Hroch, Milos; Adamcová, Michaela; Gersl, Vladimír (The Journal of pharmacology and experimental therapeutics, 2008)
Anthracycline cardiotoxicity ranks among the most severe complications of cancer chemotherapy. Although its pathogenesis is only incompletely understood, "reactive oxygen species (ROS) and iron" hypothesis has gained the widest acceptance. Besides dexrazoxane, novel oral iron chelator deferiprone has been recently reported to afford significant cardioprotection in both in vitro and ex vivo conditions. Therefore, the aim of this study was to assess whether deferiprone 1) has any effect on the anticancer action of daunorubicin and 2) whether it can overcome or significantly reduce the chronic anthracycline cardiotoxicity in the in vivo rabbit model (daunorubicin, 3 mg/kg i.v., weekly for 10 weeks). First, using the leukemic cell line, deferiprone (1-300 microM) was shown not to blunt the antiproliferative effect of daunorubicin. Instead, in clinically relevant concentrations (>10 microM), deferiprone augmented the antiproliferative action of daunorubicin. However, deferiprone (10 or 50 mg/kg administered p.o. before each daunorubicin dose) failed to afford significant protection against daunorubicin-induced mortality, left ventricular lipoperoxidation, cardiac dysfunction, and morphological cardiac deteriorations, as well as an increase in plasma cardiac troponin T. Hence, this first in vivo study changes the current view on deferiprone as a potential cardioprotectant against anthracycline cardiotoxicity. In addition, these results, together with our previous findings, further suggest that the role of iron and its chelation in anthracycline cardiotoxicity is not as trivial as originally believed and/or other mechanisms unrelated to iron-catalyzed ROS production are involved.
Keywords: Deferiprone; Male; pyridony; protinádorové látky; Anthracyclines; Cell Proliferation; HL-60 buňky; Heart Diseases; daunomycin; mužské pohlaví; králíci; Pyridones; Cardiotonic Agents; Animals; deferipron; lidé; Daunorubicin; HL-60 Cells; Humans; zvířata; kardiotonika; nemoci srdce; Rabbits; proliferace buněk; antracykliny; Antineoplastic Agents